Perlindungan Hukum Kreditor Separatis dan Peran Kurator Dalam Menjaga Keseimbangan Kreditur Dalam Proses Kepailitan di Indonesia - Siagian, Oscar Dlano; Lyanti, Merline Eva (Media Hukum Indonesia (MHI), 2025)
This paper aims to analyze the form of legal protection for separatist creditors and examine how the role of the curator in maintaining the balance between separatist creditors and other creditors in the bankruptcy process based on Law Number 37 Year 2004. In the bankruptcy process, separatist creditors have a special position because of their rights to certain guarantees, but the exercise of these rights is limited by legal provisions in order to maintain the fairness and efficiency of the bankruptcy process. On the other hand, the curator plays a central role as the manager of the bankruptcy estate with the obligation to act neutrally and fairly towards all parties. This research uses normative juridical method through statutory and jurisprudential approaches. The results of the study show that protection of secured creditors is provided through the right to execute collateral, the principle of priority, and the guarantee of a transparent process by the curator. In addition, the curator has a strategic role in maintaining the balance of rights of all creditors and preventing inequality in the distribution of bankruptcy assets.